Transfer of Lexical Cohesion in an Indonesian Translated Novel - Eka Herdiana Susanto (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2020)
This study investigates the realization of transfer of lexical cohesion implemented in the original novel into the translated one. It uses qualitative method whose data was the best-selling novel of Andrea Hirata written in Bahasa Indonesia and its English version translated by Angie Kilbane. The analysis focuses on the realization of taxonomy in lexical cohesion in the source text based on Eggins' (2004) cohesive devices categorization and its transfer into the translated version based on Newmark's (1988) translation methods. The result reveals a lot of lexical cohesive devices used by the writer in his original novel, and the most frequent appeared is similarity. Additionally, it shows some translation methods implemented in this translated version, and the most frequent is literal translation. Thus, these results support the students in preparing for translating a text and practicing within the particular criterion environment, namely academic setting.